Association between portosystemic shunts and increased complications and mortality in patients with cirrhosis - Simón-Talero, Macarena; Roccarina, Davide; Martínez, Javier; Lampichler, Katharina; Baiges, Anna; Low, Gavin; Llop, Elba; Praktiknjo, Michael; Maurer, Martin H.; Zipprich, Alexander; Triolo, Michela; Vangrinsven, Guillaume; et al. (Gastroenterology, 2018)
Advanced Chronic Liver Disease; Collateral Vessels; Portal Hypertension; Portal Pressure